(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
In the present study, a series of Indole containing the oxadiazole and thiazolidinones side chain at 3- position, is discussed. The synthesized Indole derivatives 4 (a-e), 5 (a-e) were evaluated for cardiovascular activities. Compound 3-[5’-(3”-indolomethylene)-1’,3’,4’-oxadiazol-2’-yl]-2-(p-methoxy phenyl)-4-thiazolidinone 5b, was found to be the most potent compound of the present study which showed cardiovascular activity of varying degree at dose 2.5 mg/Kg. The structures of these compounds were elucidated by IR, 1H NMR, mass spectroscopy and elemental analysis.